2012
DOI: 10.1891/216866512805000866
|View full text |Cite
|
Sign up to set email alerts
|

Policy and Systems Issues Limiting the Participation of Historically Black Colleges and Universities in the Federal Disability Research Agenda

Abstract: This study reports on an investigation of barriers that prevent Historically Black Colleges and Universities (HBCUs) from fully participating in the federal disability and rehabilitation research and development (R&D) agenda. The Delphi technique was used to examine panelists' perceptions on the importance of contextual R&D barriers ensuing from policy/systems issues across 13 different categories. The findings provide information about what Federal research entities (e.g., National Institute on Disability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…The role of self-efficacy and confidence in increasing research productivity is well documented (Bai, 2010). Moore and his colleagues (Moore, Johnson, Manyibe, Washington, Uchegbu, & Eugene-Cross, 2012; Moore, Johnson, Manyibe, Washington, Uchegbu, Eugene-Cross, et al, 2012) noted that lower levels of research self-efficacy can lead to lower rates of research productivity. Specifically, they postulated that poor U.S. federal research entity leaders’ expectations for ME research grant proposal success results in lower investigator research self-efficacy.…”
Section: Facilitators Of Research Productivitymentioning
confidence: 99%
See 4 more Smart Citations
“…The role of self-efficacy and confidence in increasing research productivity is well documented (Bai, 2010). Moore and his colleagues (Moore, Johnson, Manyibe, Washington, Uchegbu, & Eugene-Cross, 2012; Moore, Johnson, Manyibe, Washington, Uchegbu, Eugene-Cross, et al, 2012) noted that lower levels of research self-efficacy can lead to lower rates of research productivity. Specifically, they postulated that poor U.S. federal research entity leaders’ expectations for ME research grant proposal success results in lower investigator research self-efficacy.…”
Section: Facilitators Of Research Productivitymentioning
confidence: 99%
“…ME administrative culture is important in predicting investigator research productivity levels (Epps & Guidry, 2009), and can determine intellectual and capital investment decisions (Moore, Johnson, Manyibe, Washington, Uchegbu, & Eugene-Cross, 2012). Moore and his colleagues found that administrative culture was in fact the third most important challenge to research capacity and productivity at HBCUs.…”
Section: Facilitators Of Research Productivitymentioning
confidence: 99%
See 3 more Smart Citations